Modernization of the Sphere of Tourist and Hospitality Industry of the South of Russia as a Growth Factor of Socio-economic Stability of the Region - Shkurkin, Dmitry V.; Sogacheva, Olga V.; Logvencheva, Elena S.; Khramova, Marina N. (International Journal of Economics and Financial Issues, 2016)
The article presents the results of a study on the development of the service sector business management modernization concepts in the form of real practical measures in general and in relation to the corporate planning, programming, design their development. An algorithm for implementation of adaptive management as a priority the modernization tool in this area. Our study was based on the assumption that the management of the modernization and maintenance of technology in enterprises of hotel services will allow to fully realize the goals of the strategic stability of the enterprises of sphere of services, will contribute to the attainment of a new quality of development, to mobilize potentially available resources in the field of hospitality and the involvement in it of effective market mechanisms, convincingly proved that the modernization of the service sector – the update of the existing forms and methods of management, the implementation of new features companies within predictable limits. Under the modernization tools flexible management system now should be understood a process-functional management system to ensure the achievement of targets in different periods of organizational development of the company, without degradation of the resource potential, by adapting to the changing conditions of the hotel business. Keywords: tourism economics, modernization tools, flexible management, services JEL Classifications: L83, M11, Z30